Critical Thinking Development Through Digital Play: A Systematic Literature Review of Early Childhood Context: Bahasa Indonesia - Asbi, Sherllyn Azzaharra; Wulan, Sri; Utami, Ade Dwi (CV. Media Digital Publikasi Indonesia, 2026)
In today’s modern era, the world of early childhood education is inseparable from both online and offline games. Games are no longer viewed merely as tools for entertainment, but also as potential learning media that can support children’s development. The rapid advancement of technology has made digital play an integral part of children’s daily lives. Although digital games present certain challenges, they also offer notable educational benefits, particularly in fostering children’s critical thinking abilities. This study aims to systematically collect, evaluate, and analyze research related to the development of critical thinking skills in early childhood through digital games. The research employs a Systematic Literature Review (SLR) approach focusing on identifying pedagogical strategies, digital game designs, and aspects of critical thinking embedded within digital play. It also explores the teacher’s role and the empirical findings within early childhood education contexts. A total of 12 eligible studies were analyzed. The findings indicate that digital games contribute positively to the enhancement of children’s critical thinking skills. The most frequently stimulated components of critical thinking include problem-solving, logical reasoning, decision-making, independent evaluation of information, memory enhancement, and understanding of cause-and-effect relationships. Teachers play a crucial role as facilitators, companions, and guides in ensuring meaningful learning experiences through digital play. The reviewed digital games were generally designed to be both educational and interactive, highlighting the integration of learning and engagement. These findings underscore the significance of teachers’ involvement in achieving learning objectives through digital games and provide valuable insights for future curriculum development and digital educational innovation in early childhood settings.